2019
DOI: 10.1016/j.engstruct.2018.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the flexural behaviour of slim-floor beams with hollow core slabs at elevated temperature

Abstract: Slim-floor beams are a novel typology of steel beams where the steel profile is fully embedded within the concrete floor depth. While the use of this system is increasing fast in the construction practice, the available investigations on its fire performance are still scarce. This paper focuses on analysing the fire behaviour of slim-floor beams combined with hollow core slabs as flooring system. Two configurations are studied, namely Integrated Floor Beam (IFB) and Shallow Floor Beam (SFB). A finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
(23 reference statements)
0
32
0
1
Order By: Relevance
“…Previous parametric studies carried out by the authors [8,9] with a validated finite element model showed the improvement in terms of fire resistance which may be achieved with the SFB solution, as compared to an equivalent IFB configuration with the same load bearing capacity at room temperature or in terms of equal steel area. This numerical investigation confirmed that a good strategy for enhancing the fire resistance of composite beams embedded in floors is to split the lower steel flange into two steel plates.…”
Section: Code Provisions and Available Fire Design Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous parametric studies carried out by the authors [8,9] with a validated finite element model showed the improvement in terms of fire resistance which may be achieved with the SFB solution, as compared to an equivalent IFB configuration with the same load bearing capacity at room temperature or in terms of equal steel area. This numerical investigation confirmed that a good strategy for enhancing the fire resistance of composite beams embedded in floors is to split the lower steel flange into two steel plates.…”
Section: Code Provisions and Available Fire Design Methodsmentioning
confidence: 95%
“…Additionally, the most sophisticated way to evaluate the thermo-mechanical behaviour of slim-floor beams is by means of finite element (FE) models. In recent investigations, some authors [16], [8] have developed detailed FE models, using the commercial package ABAQUS, where a sequentially coupled thermal-stress analysis is performed ( Fig. 4).…”
Section: Advanced Modelsmentioning
confidence: 99%
See 3 more Smart Citations